Review on Carbon Nanotubes in Drug Therapy - Pavithra.T.K; Mahalakshmi.C.R; Hummera.R; Shashikala.V; Shwetha.T.L (Asian Journal of Pharmaceutical Research and Development, 2026)
Carbon nanotubes have gained considerable attention as advanced Nano carriers in drug therapy owing to their distinctive structural, physiochemical and biological characteristics. Their exceptionally large surface area, nanoscale size and efficient cellular internationalization facilitate high drug-loading capacity and targeted delivery of diverse therapeutic agent, including small molecules, proteins and nucleic acid. Surface modification of CNTs through covalent or non-covalent functionalization significantly improves their aqueous dispensability, biocompatibility and targeting efficiency, while simultaneously minimizing intrinsic toxicity. CNT-based drug delivery platforms enable controlled and sustained drug release, enhance bioavailability and reduce off-target effects with particular relevance in cancer treatment.